2015
DOI: 10.3390/molecules200610184
|View full text |Cite
|
Sign up to set email alerts
|

A New and Efficient Synthesis of 6-O-Methylscutellarein, the Major Metabolite of the Natural Medicine Scutellarin

Abstract: Abstract:In this paper, a new and efficient synthesis of 6-O-methylscutellarein (3), the major metabolite of the natural medicine scutellarin, is reported. Two hydroxyl groups at C-4′ and C-7 in 2 were selectively protected by chloromethyl methyl ether after the reaction conditions were optimized, then 6-O-methyl-scutellarein (3) was produced in high yield after methylation of the hydroxyl group at C-6 and subsequent deprotection of the two methyl ether groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Table 3 shows that the semisynthesis routes had fewer reaction steps compared to the total synthesis methods; however, they need tedious isolation procedures for scutellarin, which limits the scale for further chemical modification. Furthermore, their overall yields are only 6.3–10.7% [ 20 , 22 , 23 ]. For total synthesis, Kavvadias and coworkers developed a nine-step synthesis approach.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 3 shows that the semisynthesis routes had fewer reaction steps compared to the total synthesis methods; however, they need tedious isolation procedures for scutellarin, which limits the scale for further chemical modification. Furthermore, their overall yields are only 6.3–10.7% [ 20 , 22 , 23 ]. For total synthesis, Kavvadias and coworkers developed a nine-step synthesis approach.…”
Section: Resultsmentioning
confidence: 99%
“…Because of its interesting biological activity, several research groups have developed synthetic approaches to hispidulin [ 18 , 19 , 20 , 21 , 22 , 23 ]. For example, Shen and coworkers developed a strategy for semisynthesis of hispidulin in seven reaction steps by using a naturally occurring scutellarin ( Scheme 1 ) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the different reactivity of the four phenol hydroxyl groups in scutellarein (2) following the specific sequential position order 7 > 4ʹ > 6 > 5, the direct alkylation of scutellarein (2) acetone under reflux afforded three products 4, 5, and 6 in 14.8%, 28.9%, and 34.2%, respectively. The location of MOM groups in these three compounds was confirmed by 1 H-NMR and ROESY (24). For example, in the 1 H-NMR spectrum of 5 (in DMSO-d 6 ), a signal at d 12.76 indicated that the C5-OH group remained unchanged.…”
Section: Resultsmentioning
confidence: 81%